2012
DOI: 10.1002/cncr.27602
|View full text |Cite
|
Sign up to set email alerts
|

Can procalcitonin distinguish infectious fever from tumor‐related fever in non‐neutropenic cancer patients?

Abstract: BACKGROUND: Procalcitonin (PCT) has been proposed as a marker of infection and was studied in neutropenic patients. This study investigated its role in non‐neutropenic febrile cancer patients (NNCPs). METHODS: Between July 2009 and July 2010, a total of 248 NNCPs with fever were studied. PCT was measured in plasma within 24 hours of fever onset and 4 to 7 days thereafter, using a Kryptor system with a lower limit of quantitation of 0.075 ng/mL. Patients' clinical, microbiological, and radiological data were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 48 publications
5
54
0
8
Order By: Relevance
“…In this population the onset of an unknown origin fever could lead a diagnostic issue. Therefore Shomali et al explored ProCT role as a bio-marker to differentiate an infectious origin fever and a non-infectious origin fever in non-neutropenic patients with both solid tumors and hematological malignancies12. Our study aimed to defining the potential role of ProCT, used as an earlier diagnostics biomarker1314, in a cohort of patients with fever and with diagnosed solid tumor followed in our oncologic ceter consecutively.…”
mentioning
confidence: 99%
“…In this population the onset of an unknown origin fever could lead a diagnostic issue. Therefore Shomali et al explored ProCT role as a bio-marker to differentiate an infectious origin fever and a non-infectious origin fever in non-neutropenic patients with both solid tumors and hematological malignancies12. Our study aimed to defining the potential role of ProCT, used as an earlier diagnostics biomarker1314, in a cohort of patients with fever and with diagnosed solid tumor followed in our oncologic ceter consecutively.…”
mentioning
confidence: 99%
“…PCT has high accuracy in establishing or refusing a sepsis diagnosis when value PCT is below the level of 0.5 mg/l or over the level of 2.0 mg/l [30 && ]. One recent study in cancer patients showed that PCT was able to differentiate tumor-and infection-induced fever [33]. Thus, the PCT is not only a more sensitive biomarker, but also a more specific marker (with high-negative predictive value for infection) compared with CRP and ESR [31].…”
Section: Procalcitonin and Infectionmentioning
confidence: 98%
“…En este trabajo, se encontró que la concentración en suero de la procalcitonina en sujetos con una infección sistémica bacteriana (1,06 ng/mL; IC 95%, 0,075-81,95) era mayor que en los sujetos en quienes se documentó fiebre por actividad tumoral (0,67 ng/mL; IC 95%, 0,11-4,14; p= 0,033). 27 Otra estrategia que puede ser utilizada para evaluar la procalcitonina como marcador diagnóstico de sepsis en el niño con cáncer, NF, es la de cuantificar los niveles séricos de la procalcitonina en cuatro momentos que permiten establecer un patrón diferencial en su comportamiento: Grupo A) niños con diagnóstico reciente de cáncer previo al uso de quimioterapia; Grupo C) niños con neutropenia y fiebre; y Grupo D) al momento del egreso hospitalario. Esto indica que los niveles de procalcitonina son mayores en el sujeto con proceso infeccioso activo que en los individuos con actividad tumoral, y estos, a su vez, que los sujetos que se egresan del hospital.…”
Section: La Procalcitonina En Los Procesos No Infecciososunclassified